Analysis of the Decisive Factors of Government Attracting Tourists in Public Management from the Perspective of Environmental Protection - Guo, Zhicheng; Li, Yan (Problemy Ekorozwoju, 2024)
Tourism is a critical sustainable social and economic activity that can empower local communities. The current study strived to explore decisive factors that might be used it promotes environmental protection. Governments worldwide might employ to improve conservation and the tourism sector. There is a need to sponsor more publications on tourism and the environment that provide rigor, insight, and significance. There is also a need to address critical impacts, including greenhouse gases for airlines, liquid wastes for cruise ships, water and energy conservation for urban hotels, vegetation clearance, and wildlife displacement for rural resorts, and a range of direct and indirect local impacts on plants and animals for nature-based and adventure tourism in parks and wilderness areas. Governments need to work on economic models that address; currency exchange rates; airfares and taxes; land tenure and wildlife ownership laws; transport infrastructure; police, quarantine, and border security; investment law; public protected-area systems; and a variety of social pressures and fashions. The most effective means to improve environmental management in tourism is through laws and regulations for development planning, pollution control, and protected areas. In developed nations, tourism threatens conservation as property developers push to build private facilities inside public protected areas. In developing nations, tourism is a tool to fund conservation in public parks and private or communal lands. Visitors to the public, and protected areas contribute political and financial capital to park agencies. A few private tourism operators have converted areas of private and communal land to conservation.